Anesthesia and Duchenne or Becker muscular dystrophy: review of 117 anesthetic exposures. Issue 9 (6th August 2013) - Segura, Leal G.; Lorenz, Jessica D.; Weingarten, Toby N.; Scavonetto, Federica; Bojanić, Katarina; Selcen, Duygu; Sprung, Juraj; Brandom, Barbara
Summary Background Duchenne muscular dystrophy (DMD) and Becker muscular dystrophy (BMD) are associated with life‐threatening perioperative complications, including rhabdomyolysis, hyperkalemia, and hyperthermia. Current recommendations contraindicate use of succinylcholine and volatile anesthetics; however, the latter recommendation remains controversial. Objective To review the perioperative outcomes of patients with DMD and BMD. Methods We reviewed records of patients with DMD or BMD who underwent anesthetic management at our institution from January 1990 through December 2011. Results We identified 47 patients (DMD, 37; BMD, 10) who underwent 117 anesthetic exposures (DMD, 101; BMD, 16). Volatile anesthetic agents were used 66 times (DMD, 59; BMD, 7). One patient with undiagnosed BMD received succinylcholine and developed acute rhabdomyolysis and hyperkalemic cardiac arrest. All other major complications were attributed to the procedure (i.e., large bleeding), to preexisting comorbidities (i.e., respiratory failure, cardiac disease), or to both. Conclusions Use of succinylcholine in children with dystrophinopathy is contraindicated. These patients have significant comorbidities and are frequently undergoing extensive operations; complications related to these factors can develop, as evidenced by our series. These complications may occur with use of volatile and nonvolatile anesthetics. However, because most of our patients were older than 8 years at the time of surgery, our observation cannot be generalized to younger dystrophin‐deficient children.